Progress in vaccination towards hepatitis B control and elimination in the Region of the Americas - Alba Maria Ropero Álvarez; Silvia Pérez-Vilar; Carmelita Pacis-Tirso; Marcela Contreras; Nathalie El Omeiri; Cuauhtémoc Ruiz-Matus; Martha Velandia-González (BMC, 2017)
Abstract Background Over recent decades, the Region of the Americas has made significant progress towards hepatitis B elimination. We summarize the countries/territories' efforts in introducing and implementing hepatitis B (HB) vaccination and in evaluating its impact on HB virus seroprevalence. Methods We collected information about HB vaccination schedules, coverage estimates, and year of vaccine introduction from countries/territories reporting to the Pan American Health Organization/World Health Organization (PAHO/WHO) through the WHO/UNICEF Joint Reporting Form on Immunization. We obtained additional information regarding countries/territories vaccination recommendations and strategies through communications with Expanded Program on Immunization (EPI) managers and national immunization survey reports. We identified vaccine impact studies conducted and published in the Americas. Results As of October 2016, all 51 countries/territories have included infant HB vaccination in their official immunization schedule. Twenty countries, whose populations represent over 90% of the Region's births, have included nationwide newborn HB vaccination. We estimated at 89% and 75%, the regional three-dose series and the birth dose HB vaccination coverage, respectively, for 2015. The impact evaluations of infant HB immunization programs in the Region have shown substantial reductions in HB surface antigen (HBsAg) seroprevalence. Conclusion The achievements of vaccination programs in the Americas suggest that the elimination of perinatal and early childhood HB transmission could be feasible in the short-term. Moreover, the data gathered indicate that the Region may have already achieved the 2020 WHO goal for HB control.